THE PROFICIENCY ORIENTATION OF EXISTING METHODOLOGIES: A PRELIMINARY APPROACH TO THE TEACHING OF ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA - Dewa Komang Tantra (ISSN)
Principles and priorities in language teaching have shifted and changed over the years, often in response to paradigm shifts in linguistics and learning theory. Historically, methods that adhere to empiricist viewpoints have contrasted sharply with those that derive from a rationalist perspective of human learning. The various methodologies and approaches reviewed thus far have experienced differential success and popularity among practitioners. Today, many teachers are adopting an eclectic approach to language learning and teaching, believing that the age-old search for the ‘one true way’ can be futile and frustrating. As we realize that learning is an extremely complex process and that learners are individuals with different personalities, styles, and preferences, we have begun to look for a multiplicity of ways to respond to the challenge of teaching. Eclecticism, however, needs to be principled if instruction is to be effective, and techniques and activities need to be chosen intelligently to relate to specific program objectives. This paper proposes some general principles that might orient our teaching of English in Indonesia toward proficiency goals. The hypothesized principles focus on providing instruction that is meaningful, interactive, and responsive to learner needs.